Evaluation of Trichoderma atroviride endophytes with growth-promoting activities on tomato plants and antagonistic action on Fusarium oxysporum - Schoffen, Rodrigo Pawloski; Ribeiro, Amanda da Silva; Oliveira-Junior, Verci Alves de; Polonio, Julio Cesar; Polli, Andressa Domingos; Orlandelli, Ravely Casarotti; Ribeiro, Marcos Alessandro dos Santos; Pamphile, João Alencar; Azevedo, João Lúcio (Ciência e Natura, 2020)
In Brazil, tomato is one of the most consumed vegetables and the fungus Fusarium oxysporum is one of the most important phytopathogen of tomato plants (Lycopersicon esculentum Mill.). Thus, the search of beneficial microorganisms with growth-promoting and/or biological control properties represent an important tool for agricultural biotechnology. Herein, two Trichoderma endophytes (strains 36b and 164b) associated with Coffea arabica were investigated on their growth-promoting activities on plants and their antagonist effects and interactions against F. oxysporum. Molecular multigene (ITS- TEF-TUB-CAL) identification and phylogenetic analysis allowed the identification of these endophytes as belonging to Trichoderma atroviride species. When inoculated with the endophytic strain 36b, tomato plants reached the highest speed of seedling emergence (83.3%), but both endophytes increased the number of leaves, root length and dry biomass of treated plants. Regarding the in vitro antagonism assay, reduced phytopathogen growth by approximately 70 (strain 36b) and 52% (strain 164b) which indicates a partial replacement of endophytes after initial deadlock with mycelial contact. Scanning electron microscopy allowed to observe the presence of Fusarium macroconidia between endophytic hyphae and conidia, with the helicoidization of endophytic hyphae, which wrapped around the pathogen hyphae, suggesting a mechanical inhibition by strangulation.